Pengaruh Faktor Sosial dan Psikologis Terhadap Proses Penjualan Sayuran Hidroponik di Kelompok Tani Kosaghra Lestari - Ardelia, Nabila Abidah; Setyadi, Taufik; Wijayati, Prasmita Dian (Universitas Muhammadiyah Pontianak, 2025)
This study analyzes the influence of social and psychological factors on the sales process of hydroponic vegetables at the Kosaghra Lestari Farmer Group. Using a quantitative approach with SEM-PLS analysis on 30 purposively selected respondents, results show both factors significantly and positively affect sales. Social norms are the dominant indicator, while perception is strongest for psychological factors. The findings highlight that community-based marketing strategies and building positive consumer perceptions are essential to improve sustainable sales effectiveness.